2013
DOI: 10.2135/cropsci2012.05.0277
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Genotype × Environment Interaction Analysis for Agronomical and Some Morphological Traits in Half‐Sib Families of Tall Fescue

Abstract: Tall fescue (Festuca arundinacea Schreb.) is an outcrossing allohexaploid grass species extensively used for forage and turf worldwide. Twenty‐five genotypes of tall fescue were chosen from a broad‐base population and the genetic diversity was evaluated based on expressed sequence tag‐simple sequence repeat molecular markers and agronomical and morphological traits. Their respective half‐sib polycross progenies were also evaluated for these same traits at six environments (two locations for 3 yr). The high gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
42
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 41 publications
8
42
0
Order By: Relevance
“…Dry matter yield had significant and positive correlations with PH, IL, NS, and ProC under both moisture environments. According to previous studies by Majidi et al (2009) and Amini et al (2013) in tall fescue and Wilkins (1985) in perennial ryegrass (Lolium perenne), plant dry matter yield is positively correlated with plant height. Turk and Celik (2006) observed significant and positive correlations among dry matter yield, number of stems per plant and plant height in sainfoin.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Dry matter yield had significant and positive correlations with PH, IL, NS, and ProC under both moisture environments. According to previous studies by Majidi et al (2009) and Amini et al (2013) in tall fescue and Wilkins (1985) in perennial ryegrass (Lolium perenne), plant dry matter yield is positively correlated with plant height. Turk and Celik (2006) observed significant and positive correlations among dry matter yield, number of stems per plant and plant height in sainfoin.…”
Section: Discussionmentioning
confidence: 78%
“…Correlations among traits have been estimated in many forage plants (Majidi et al, 2009;Amini et al, 2013;Araghi et al, 2014). In addition, selection could be practiced on a highly heritable trait that is correlated to a more complex trait such as yield with a lower heritability.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, different estimates of heritability were obtained for the S 1 and OP progenies and parental clones. Traits under complex genetic control, such as forage yield, have reportedly low to moderate heritability values, whereas high values have been obtained for others such as PH (Majidi et al, 2009;Amini et al, 2013;Araghi et al, 2014). In the S 1 progenies, moderate to high values of broad-sense heritability (>0.5) were recorded for DIE, DA, PH, NS, spread, and TDMY, whereas moderate to low values were measured for DMYC1, DMYC2, and MPDM.…”
Section: Genetic Analysis Of Traitsmentioning
confidence: 99%
“…Synthetic varieties need a firm level of phenotypic homogeneity to pass variety trials and also a high level of heterozygosity to maximize adaptability and agronomic performance. Therefore, finding the optimal level of diversity in synthetic cultivars is very important (Amini et al, 2013). Molecular markers offer powerful tools for the analysis of genetic diversity independent of the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular marker assisted parental selection may allow optimization of parental combinations in order to maximize heterosis and to minimize inbreeding. In perennial ryegrass (Kölliker et al, 2005), tall fescue (Amini et al, 2013) selection of genetically diverse parents based on molecular markers was shown to lead to better agronomic performance in first and second generation progenies. Identifying varieties with salinity tolerance may offer opportunities for future breeding efforts and provide growers with increased flexibility for cultivation area.…”
Section: Introductionmentioning
confidence: 99%